2022
DOI: 10.3390/cimb44090274
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Angiogenic Markers in Gastroenteropancreatic Neuroendocrine Neoplasms: A Systematic Review

Abstract: Background: Neuroendocrine neoplasms are a heterogeneous group of tumors that raise challenges in terms of diagnosis, treatment and monitoring. Despite continuous efforts, no biomarker has showed satisfying accuracy in predicting outcome or response to treatment. Methods: We conducted a systematic review to determine relevant circulating biomarkers for angiogenesis in neuroendocrine tumors. We searched three databases (Pubmed, Embase, Web of Science) using the keywords “neuroendocrine” and “biomarkers”, plus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…VEGF signalling pathways in NENs are one of the most studied angiogenic factors. Controversial conclusions have been obtained from the analysed data [ 29 ]. Some studies showed higher VEGF levels in NET patients compared to healthy controls, however, with a lack of correlation between grading and aggressiveness [ 10 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF signalling pathways in NENs are one of the most studied angiogenic factors. Controversial conclusions have been obtained from the analysed data [ 29 ]. Some studies showed higher VEGF levels in NET patients compared to healthy controls, however, with a lack of correlation between grading and aggressiveness [ 10 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, placental growth factor, angiopoietin 2, and IL-8 were found to be good predictors of unfavorable outcomes and aggressive disease behavior. However, there is currently no evidence to use them as routine markers in the clinic [109].…”
Section: Other Biomarkersmentioning
confidence: 99%